IMPLEMENTATION OF THE ADDIE MODEL (ANALYSIS, DESIGN, DEVELOPMENT, IMPLEMENTATION, EVALUATION) IN PHP-BASED E-LEARNING IN THE ERA OF PANDEMIC - Muhammad Rusdi; Haji Sirajuddin; Rina Alfah (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2022)
During the pandemic period at the beginning of 2020, the effects are still felt until now. All schools in Indonesia may even be closed for almost 2 (two) semesters. At times like this, every teacher inevitably is required to use E-learning without face-to-face with students. The use of various media such as Whatsapp, Zoom, Google meet and Clasromm ect is very helpful for teachers and students. In this phenomenon, we conducted research using the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) on PHP-based e-learning that we designed and created, to support the government movement that still implements distance learning more easily. With the E-Learning Application that has been created, it is very helpful for teachers, students and administrative staff in data management, especially for online learning (on the network) during this pandemic period. This PHP-based E-Learning application can be a choice of E-Learning media for schools that are still unable to do face-to-face learning directly.